2013
DOI: 10.1590/s0103-84782013001000008
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade fisiológica de sementes de citros durante o armazenamento em ambiente refrigerado

Abstract: Objetivou-se avaliar o efeito do armazenamento sobre a viabilidade das sementes dos porta-enxertos Citradia 1708, Citrandarin 1710, Citrange Carrizo, limoeiro Cravo, Trifoliata Limeira, Rangpur x Swingle 1707 armazenadas em sacolas de polietileno de alta densidade (PEAD) sobre temperatura controlada de 5-7°C e umidade relativa do ar de 70% por 210 dias. Inicialmente e a cada 30 dias foram avaliadas a emergência, índice de velocidade de emergência e o grau de umidade das sementes. O delineamento experimental ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Struiving et al (2013).These authors reported values of 125.0 g of 1000 seeds of citrandarin 1710 (C. reticulata -Changsha x P. trifoliata -English Small), a value similar to those obtained for citrandarins TSxPT 222, 254, 281 and 282. All rootstocks in this study had final emergence rate (FER) above 84%, with no statistical differences between them, with citrandarins TSxPT 123, 254 and 282, together with Rangpur lime and Swingle citrumelo, reaching 100 % FER (Table 3).…”
supporting
confidence: 63%
“…Struiving et al (2013).These authors reported values of 125.0 g of 1000 seeds of citrandarin 1710 (C. reticulata -Changsha x P. trifoliata -English Small), a value similar to those obtained for citrandarins TSxPT 222, 254, 281 and 282. All rootstocks in this study had final emergence rate (FER) above 84%, with no statistical differences between them, with citrandarins TSxPT 123, 254 and 282, together with Rangpur lime and Swingle citrumelo, reaching 100 % FER (Table 3).…”
supporting
confidence: 63%
“…The emergence of seeds extracted from fruits harvested at 180 DAA increased during cold storage (Figure 4 C). Struiving et al (2013) also observed loss of vigor of 'Limeira' trifoliate orange seeds, after storing seeds already extracted from fruits of this rootstock, in this case attributed to the reduction of seed water content.…”
Section: Physiological Quality Of Seedsmentioning
confidence: 67%
“…Cold storage of fruits may have broken seed dormancy. According to Struivingi et al (2013), some varieties of citrus rootstocks have some kind of dormancy, presenting problems of germination uniformity. Dormancy may be caused by seed coat, acting as a physical barrier to water imbibition and gas diffusion, or by the presence of an embryo development inhibitor in the seed coat.…”
Section: Seed Germination and Emergencementioning
confidence: 99%